Design and evaluation of an instrumented microfluidic organotypic device and sensor module for organ-on-a-chip applications - Richardson, Alec Evan, author; Henry, Charles, advisor; Tobet, Stuart, advisor; Bark, David, committee member; Abdo, Zaid, committee member (Colorado State University. Libraries, 2020)
Organ and tissue-on-a-chip technologies are powerful tools for drug discovery and disease modeling, yet many of these systems rely heavily on in vitro cell culture to create reductionist models of tissues and organs. Therefore, Organ-on-chip devices recapitulate some tissue functions and are useful for high-throughput screening but fail to capture the richness of cellular interactions of tissues in vivo because they lack the cellular diversity and complex architecture of native tissue. This thesis describes the design and testing of 1) a microfluidic organotypic device (MOD) for culture of murine intestinal tissue and 2) a microfluidic sensor module to be implemented inline with the MOD for real-time sensing of analytes and metabolites. The MOD houses full-thickness murine intestinal tissue, including muscular, neural, immune, and epithelial components. We used the MOD system to maintain murine intestinal explants for 72 h ex vivo. Explants cultured in the MOD formed a barrier between independent fluidic channels perfused with media, which is critical to recapitulating intestinal barrier function in vivo. We also established differential oxygen concentrations in the fluidic channels and showed that more bacteria were present on the tissue's mucosal surface when exposed to near-anoxic media. The sensor module is a reversibly sealed microfluidic device with magnetic connections that can withstand high backpressures. Further, electrodes housed in commercial finger-tight fittings were integrated into the sensor module in a plug-and-play format. Future work will include developing electrochemical/optical sensors for various biological compounds relevant to intestinal physiology. Ultimately, the MOD and sensor module will be implemented in long-term microbiome studies to elucidate the relationship among microbial, epithelial, neuro and immune components of the gut wall in health and disease.